Some Aspects of Radial Graphs Under Boolean Operations - Vetriselvi, S.; Sangeetha, G. (Communications in Mathematics and Applications, 2024)
Two vertices of a graph \(G\) are said to be radial to each other if the distance between them is equal to the radius of the graph. The radial graph of a graph \(G\), denoted by \(R(G)\), has the vertex set as in \(G\) and two vertices are adjacent in \(R(G)\) if and only if they are radial to each other in \(G\). If \(G\) is disconnected, then the two vertices are adjacent in \(R(G)\) if they belong to different components of \(G\). The main objective of this paper is to determine the radial graphs of some families of product graphs.
Keywords: Radial graph; Conjunction; Rejection; Cartesian product